Epidemiology of Time-Loss Injuries in Senior and Under-18 Portuguese Male Rugby Players - Ferreira, António Miguel da Cruz (2020)
Rugby union has one of the highest injury incidence rates in team sports, however, most of the available data focus on the epidemiology of injuries in countries where rugby is popular. We aimed to report the incidence rate and relevant epidemiological aspects of injuries occurred in a group of Portuguese male rugby players. A prospective cohort study was conducted with a group of 45 senior and 32 under-18 male players (total of 77 players). Outcome measures included injury incidence, position, type, location and severity of injuries. The match injury incidence for all players was 55.84 per 1000 player match-hours (66.66 for seniors, 42.85 for under-18), while mean time-loss for injury was 20.79 days. No statistical differences were found between groups. Lower limb injuries accounted for 60.5% of all injuries, while joint/ligament injuries were the most prevalent type. Contact events were responsible for 65.1% of injuries. Despite the limitations, the obtained data are consistent with the literature. Time-loss injuries seem highly prevalent in rugby union and the incidence rates found in this Portuguese-based study were lower than the reported for international and senior men's professional rugby union, but higher than those occurring in community rugby in tier-1 countries. The authors believe these data reinforce the need to develop and implement effective injury surveillance and prevention programs.